2017
DOI: 10.3390/v9120365
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Encoded miR-US25-1-5p Attenuates CD147/EMMPRIN-Mediated Early Antiviral Response

Abstract: Cellular receptor-mediated signaling pathways play critical roles during the initial immune response to Human Cytomegalovirus (HCMV) infection. However, the involvement of type-I transmembrane glycoprotein CD147/EMMPRIN (extracellular matrix metalloproteinase inducer) in the antiviral response to HCMV infection is still unknown. Here, we demonstrated the specific knockdown of CD147 significantly decreased HCMV-induced activation of NF-κB and Interferon-beta (IFN-β), which contribute to the cellular antiviral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Additionally, miR-UL148D was found to target ACVR1B and limited pro-inflammatory cytokine secretion in HCMV latent infected primary myeloid cells [66]. Besides miR-UL112-1 and miR-UL148D, a very recent work confirmed that miR-US25-1-5p could attenuate the expression of CD147, which can mediate HCMV-triggered antiviral signaling, and induce HCMV lytic propagation at a low multiplicity of infection [67].…”
Section: Biological and Pathophysiological Functions Of Hcmv Mirnasmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, miR-UL148D was found to target ACVR1B and limited pro-inflammatory cytokine secretion in HCMV latent infected primary myeloid cells [66]. Besides miR-UL112-1 and miR-UL148D, a very recent work confirmed that miR-US25-1-5p could attenuate the expression of CD147, which can mediate HCMV-triggered antiviral signaling, and induce HCMV lytic propagation at a low multiplicity of infection [67].…”
Section: Biological and Pathophysiological Functions Of Hcmv Mirnasmentioning
confidence: 95%
“…Essential hypertension has been recognized as a critical risk factor for cardiovascular diseases and the main cause of chronic renal failure. Existing studies have documented that essential hypertension may be induced by specific environmental and genetic factors, nevertheless, the precise cause of [27], [49] IL-32 Immune evasion [50] hcmv-miR-US4-1 ERAP1 Immune evasion [29] hcmv-miR-UL112-5p ERAP1 Immune evasion [51] hcmv-miR-UL112-3p IE72 Virus replication [24] UL114 Virus replication [52] hcmv-miR-US25-2 Undetermined Virus replication [52] hcmv-miR-US25-1 Undetermined Virus replication [52] hcmv-miR-US25-2 eIF4A1 Virus replication [53] hcmv-miR-US25-1 ATP6V0C Virus replication [54] hcmv-miR-US25-1 YWHAE, UBB, NPM1, HSP90AA1 Virus replication [55] hcmv-miR-US33-5p STX3 Virus replication [56] hcmv-miR-US5-1 Geminin Virus replication [57] hcmv-miR-UL112-3p IE1 HCMV latency [59] IE72 HCMV latency [60] hcmv-miR-UL148D IER5 HCMV latency [61] hcmv-miR-UL112-3p Type I IFNs Host secretory pathway [62] TLR2 Host secretory pathway [63] hcmv-miR-UL148D RANTES Host secretory pathway [65] ACVR1B Host secretory pathway [66] hcmv-miR-US25-1 CD147 Host secretory pathway [67] hcmv-miR-UL148D IEX-1 Host cell apoptosis [68] ERN1 Host cell apoptosis [70] hcmv-miR-UL36-5p ANT3 Host cell apoptosis [73] hcmv-miR-US4-1 QARS Host cell apoptosis [74] hcmv-miR-US25-1 BRCC 3 Host cell apoptosis [75] hcmv-miR-UL112-3p MAPK, Chemokine Host cell growth and proliferation [31] hcmv-miR-US25-1-5p, hcmv-miR-US25-2-5p Plasma Congenital CMV infection Upregulation [84] hcmv-miR-US33-5p Plasma Acute aortic dissection Upregulation [86] hcmv-miR-US4-1, hcmv-miR-UL-148D Serum IFNα treatment non-responsive chronic hepatitis B Upregulation [87] hcmv-miR-UL112-3p, hcmv-miR-UL22a-5p, hcmv-miR-UL148d, hcmv-miR-UL36-5p, hcmv-miR-UL59…”
Section: Altered Hcmv-derived Mirnas In Circulation Can Be Served As mentioning
confidence: 99%
“…miR-UL112, US25-2-3p, and US4-1 modulate immune recognition by cytotoxic T lymphocyte (CTL) and natural killer (NK) cells (64)(65)(66)(67). Similarly, the HCMV miRs UL112-3p, US5-1, UL112-1, US25-1-5p, and UL148D target multiple host inflammatory genes and result in reduced inflammatory response (53,54,(68)(69)(70)(71). Also, UL148D and UL36-5p are found to inhibit programmed cell death by repressing the expression of cellular genes involved in the regulation of apoptosis (72)(73)(74).…”
Section: β-Herpesvirus-encoded V-mirnasmentioning
confidence: 99%
“…In recent years, primary myeloid cells have been receiving much attention due to the high ranges of latency-associated HCMV transcripts including miRNAs measured in this cell model, while much work on the potential targets of these HCMV miRNAs has been carried out [30,31,49]. Various experiments have been performed to elucidate the expression and functions of miRNAs during latency using primary myeloid cells infected with mutant viruses [21,27,31,51,52]. The mutation include altering the expression of a specific miRNA or removing the miRNA binding site.…”
Section: Main Textmentioning
confidence: 99%